(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
This study presents an integrated geochemical, petrographic, and thermogravimetric assessment of Cretaceous–Cenozoic coal deposits from the Benue Trough, Nigeria, with the objective of characterizing their combustion behavior and evaluating their suitability for thermal power generation. The Benue Trough is a major NE–SW trending intracontinental rift basin extending from the Gulf of Guinea to the Chad Basin and hosts significant coal-bearing successions of economic importance. Despite the global transition toward low-carbon energy systems, coal remains a strategic component of the global energy mix, particularly in developing economies where energy demand continues to increase and infrastructure for renewables remains limited. Twenty-nine representative coal samples collected from multiple sub-basins within the trough were subjected to proximate analysis, total sulfur determination, bomb calorimetry, reflected-light petrography (maceral quantification), and thermogravimetric analysis (TGA). Proximate data indicate generally high volatile matter contents and low ash yields, consistent with sub-bituminous to high-volatile bituminous rank. The average gross calorific value is 24.82 MJ/kg, suggesting moderate-to-high energy potential. Total sulfur contents are generally low to moderate, supporting their potential for relatively cleaner combustion compared to high-sulfur coals. Petrographic examination reveals that the organic fraction is dominated by vitrinite (mean 59.3 vol.% on a mineral-matter-free basis), indicating significant contribution from woody precursor material deposited under predominantly reducing conditions. Inertinite contents show marked variability across the Upper, Middle, and Lower Benue sub-regions, reflecting spatial differences in paleofire intensity, oxidation conditions, and depositional regimes. Liptinite macerals are sparse and notably absent in samples from the Middle Benue Trough, suggesting limited preservation of hydrogen-rich algal or resinous components. Thermogravimetric profiles demonstrate characteristic devolatilization and combustion stages consistent with vitrinite-rich coals. Except for samples 01 and 17, which exhibit anomalously high ash yields (73.03 wt.% and 81.57 wt.%, respectively) and are thus unsuitable for efficient combustion, the majority of the samples meet fundamental criteria for coal-fired power applications. Overall, the results establish that most Benue Trough coals possess favorable combustion characteristics and calorific properties, supporting their strategic potential for domestic power generation and energy security in Nigeria.